Jambi City Tourism Information System Design - Rezagi Meliano; Tanto (Jurnal AKSI (Akuntansi dan Sistem Informasi), 2021)
The very rapid development of technology helps a lot in terms of disseminating information to be faster, more accurate, and not limited by place and time. Technology in the tourism sector is not only used as a promotional medium, but technology is also a learning medium for entrepreneurs in the tourism sector so it is important for the tourism sector to have an information system as a medium for disseminating information. The Jambi City Tourism Information System is an information system that contains a collection of information data that summarizes information about the region, province or tourism place in the city of Jambi which is compiled in a web-based information system, with this information system it can make it easier for the public to obtain information, accelerating the service of information sources. The design of the tourism information system in the city of Jambi is built in a web-based form with system design assisted by several tools such as the programming language PHP, Javascript, MySQL, Xampp, and Adobe Dreamweaver.